NMDA Receptor-Antagonistic Properties of Hyperforin, a Constituent of St. John's Wort - Vikas Kumar; Alexander Mdzinarishvili; Cornelia Kiewert; Thomas Abbruscato; Ulrich Bickel; Cornelis J. van der Schyf; Jochen Klein (Elsevier, 2006)
Extracts of the medicinal plant St. John's wort (Hypericum perforatum) are widely used for the treatment of affective disorders. Hyperforin, a constituent of St. John's wort, is known to modulate the release and re-uptake of various neurotransmitters, an action that likely underlies its antidepressive activity. We now report that hyperforin also has N-methyl-D-aspartate (NMDA)-antagonistic effects. Hyperforin (10 µM) was found to inhibit the NMDA-induced calcium influx into cortical neurons. In rat hippocampal slices, hyperforin inhibited the NMDA-receptor-mediated release of choline from phospholipids. Hyperforin also antagonized the increase of water content in freshly isolated hippocampal slices, and it counteracted, at 3 and 10 µM, the increase of water content induced by NMDA. Hyperforin was inactive, however, in two in vivo models of brain edema formation, middle cerebral artery occlusion and water intoxication in mice. In conclusion, hyperforin has NMDA-receptor-antagonistic and potential neuroprotective effects in vitro. This effect may contribute to the therapeutic effectiveness of St. John's wort extracts in some situations, for example, for relapse prevention in alcoholism. Keywords:: edema, fura-2, hippocampal slice, middle cerebral artery occlusion, water intoxication